(untitled) ("Conference on Universal Science Research 2023", 2023)
Stylistic devices can also be called rhetorical devices because they are often used in rhetoric, the discipline that covers effective and persuasive language use. Stylistic devices can also be called figures of speech because they often involve non-literal or figurative language. By carefully selecting and employing techniques such as metaphors, similes, alliteration, and personification, writers can craft a rich tapestry of language that captivates the senses and leaves a lasting impact on the reader. The most famous examples are alliteration, assonance and puns. Order-related rhetorical devices: these devices modify the normal order of words within a phrase or sentence. The most well-known examples are anaphoras, anastrophes, asyndeton, chiasmus, omissions, hyperbaton and polysyndeton .